Constructing futures, enhancing solutions: Stakeholder-driven scenario development and system modeling for climate-change challenges - Williams, Paula; Kliskey, Andrew Anaru; Cronan, Daniel; Trammell, E. Jamie; de Haro-Martí, Mario E.; Wilson, Jayde (Frontiers in Environmental Science, 2023)
Finding effective and practical solutions to climate change challenges in food-energy-water systems requires the integration of experts in local/regional social and biophysical systems, and these are commonly local community members. In the Magic Valley, Idaho we investigated the tensions between water used for energy and to irrigate food, as well as, strategies for protecting water quantity and quality. Incorporating stakeholders with long-standing expertise allows the development of solutions to these challenges that are locally and regionally practical and consistent with the values of the social system into which they are incorporated. We describe a stakeholder-driven process used in a case study in the Magic Valley that incorporated local experts to develop plausible future scenarios, identify drivers of change, vet impact and hydrological modeling and map areas of change. The process described allowed stakeholders to envision alternative futures in their region, leading to development of enhanced context and place-based solutions and an anticipated time line for adoption of those solutions. The solutions developed by the stakeholders have been applied across many geographic areas. The described process can also be applied across a broad range of geographic levels.